Tingkat Demokrasi Kepemimpinan dalam Pengelolaan Subak Lodtunduh di Kecamatan Ubud Kabupaten Gianyar - FAIRUZ HSB, IQBAL; WINDIA, I WAYAN; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Level of Democratic Leadership in the Management of Subak Lodtunduh in District of Ubud, Gianyar Regency.  Democracy in subak management leadership is very important to achieve the main objectives of subak, democratic values will lead to the participation of members of the subak itself. Through democracy, subak members will participate in the sustainability of subak, and the goals of the subak organization itself will be sustainable. Democratic leadership is active, dynamic and directed leadership that allows each member to actively participate. The purpose of this study is to determine the level of democracy that has been carried out in the management leadership of Subak Lodtunduh, in District of Ubud, Gianyar Regency. This study combined qualitative and quantitative research. The variable of this study is to measure democratic values of leadership in the management of SubakLodtunduh. The variables, indicators, parameters and measurements of this study are to measure the level of democratic leadership in the management of Subak Lodtunduh 1) Accept criticism and suggestions from members 2) Prioritizing deliberation for consensus 3) Not acting arbitrarily on members 4) Activities carried out in a transparent and sustainable manner 5) Subak members are willing to participate. The results showed that the level of democratic leadership in managing Subak Lodtunduh is categorized very good, with an average score of 94.12%. It can be concluded that the variable level of democratic leadership in subak through the indicator of democracy run by the leader (Pekaseh) has a very good category. This means that the level of democratic leadership run by Pekaseh in the management of Subak Lodtunduh has been very good so that the sustainability of Subak Lodtunduh can be maintained and if there is a change of personnel in the subak management, democratic leadership needs to be maintained.